2017
DOI: 10.3390/ijms19010022
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Breed, Feeding Status, and Diet on Adipogenic, Lipogenic, and Lipolytic Gene Expression in Growing Iberian and Duroc Pigs

Abstract: Meat quality depends on tissue composition which is in turn influenced by different factors, such as diet, genotype, age, or sex. We evaluated the effects of breed, 24 h fasting, and dietary energy source (HO: oleic acid versus CH: carbohydrates) on the expression of candidate genes involved in adipogenesis, lipogenesis, and lipolysis in the adipose tissue from Iberian and Duroc growing pigs. The Iberian pigs showed greater feed intake, backfat thickness, and saturated fatty acids (SFA) content in the subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
44
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 63 publications
9
44
1
6
Order By: Relevance
“…LEP targets peripheral tissues favouring FA catabolism over lipogenesis and it has been suggested that leptin can regulate adipose tissue metabolism by autocrine signalling [67]. As in other studies with the Iberian pig breed [52,68,69], genetically similar to AL, compared to the leaner Duroc and Landrace breeds, LEP gene was found significantly overexpressed in the AL pig (log2 FC = 1.376, q < 0.05). This is in agreement with its recognized fatter phenotype and, very similar to the IB breed, suggesting the development of leptin resistance [27,52].…”
Section: Gene Expression Analysis: Deseq2supporting
confidence: 50%
“…LEP targets peripheral tissues favouring FA catabolism over lipogenesis and it has been suggested that leptin can regulate adipose tissue metabolism by autocrine signalling [67]. As in other studies with the Iberian pig breed [52,68,69], genetically similar to AL, compared to the leaner Duroc and Landrace breeds, LEP gene was found significantly overexpressed in the AL pig (log2 FC = 1.376, q < 0.05). This is in agreement with its recognized fatter phenotype and, very similar to the IB breed, suggesting the development of leptin resistance [27,52].…”
Section: Gene Expression Analysis: Deseq2supporting
confidence: 50%
“…Likewise, the ME1 gene has been implicated in PUFA biosynthesis [136][137][138]. Furthermore, in animal models, the ME1 gene expression is strongly regulated by the dietary fat content [125,139]. Fat content of the low or high adherence group (high adherence characterized by a high fish intake, nuts, olive oil, and a low intake of red meat and other products rich in SFA) may modulate the effects of the ME1 polymorphisms on serum omega-3 PUFA (as well as on the omega-6/omega-3 ratio), contributing to explain the statistical signal.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in lipogenic enzyme activity between lean and fatty pig breeds during the fattening period have been pointed out by several authors [ 51 , 52 ], which lead to a more intense lipid metabolism [ 15 ] and greater capacity for tissue lipid synthesis in fatty pigs, such as Iberian pigs, as compared to conventional pigs [ 53 ]. The effect of animal tissue, muscle, and adipose tissue on lipogenic enzyme activity is also well known [ 13 , 23 ], which would suggest different regulatory lipid metabolism mechanisms for subcutaneous and intramuscular fat [ 15 ].…”
Section: Discussionmentioning
confidence: 99%